Trends and Constraints on Brazilian Photovoltaic Industry: Energy Policies, Interconnection Codes and Equipment Certification - Marafao, Fernando Pinhabel; dos Santos Alonso, Augusto Matheus; Goncalves, Flavio A. S.; Morales Paredes, Helmo Kelis; Martins, Antonio Cesar Germano; Brandao, Danilo Iglesias (Institute of Electrical and Electronics Engineers (IEEE), 2018)
After years of dormant scenario, the Brazilian industry of photovoltaic (PV) energy systems is now growing fast. Therefore, improving interconnection and certification codes, as well as standards, has become undeniably important to establish a well-regulated market under concern of businesses, equipment and power quality matters. Thus, considering international standards and world-recognized scenarios for distributed PV systems, this paper aims to discuss the existing local energy regulations, grid connection codes, and other related limitations that restrain a faster market and technology development in Brazil. Special attention is given to the certification requirements for grid-connected inverters and other PV equipment, along with the new trends in energy policies, focusing on their impacts on Brazilian PV industry. In the end, it demonstrates that despite its current underdeveloped status, the Brazilian scenario is expected to be quite enthusiastic in the following years and may represent an attractive and dynamic market for professionals, companies and energy investors.
Keywords: Brazilian DG rules; Certification; Distributed generation; Energy policies; Finance; Generators; Industries; Inverters; Microgeneration; Photovoltaic; Power generation; PV certification; PV equipment; Renewable energy; Standards